Chemical Control of Marmorated Stink Bug (Halyomorpha halys Stål) in Pear Orchards with Integrated Pest Management - Paušič, Andrej; Goričan, Jernej; Lešnik, Mario (Agricultura Scientia, 2025)
In the growing seasons of 2021 and 2022, two field experiments in a Williams pear and an Abate Fetel pear orchard were conducted at location Bilje near Nova Gorica. The effectiveness of two spraying programs for suppressing the marmorated stink bug (MSB) was analyzed. In program A, insecticides based on the active substances acetamprid, pyriproxyfen, spirotetramat, indoxacarb, lambda-cyhalothrin, and abamectin were used. In program B, insecticides based on the active substances acetamprid, pyriproxyfen, deltamethrin, phosmet, and abamectin were used, combined with alternative repellent preparations. In 2021, we had 23 % of fruit damaged by MSB in the Williams variety and 25% in the Abate Fetel variety, both in the untreated control plots. In 2022, the percentage of fruits damaged by MSB in the control plots was 30 % in the Williams variety and 30% in the Abate Fetel variety. The effectiveness of spraying program A in reducing the proportion of damaged fruit by MSB was 34 to 78 % in 2021 and 60 to 70 % in 2022. The effectiveness of spraying program B in reducing the proportion of damaged fruit was 34 to 78 % in 2021 and 60 to 70 % in 2022. We can not entirely prevent economically relevant crop losses with the tested spray programs.